(untitled) (International Journal of Scientific Research in Science and Technology, 2024)
In response to the increasing global energy demand, developing cost-effective and reliable renewable energy sources is crucial. Dye-Sensitized Solar Cells (DSSCs) have emerged as a promising alternative due to their low production cost, flexibility, and capability to operate under diffuse sunlight. This study aims to enhance the efficiency of DSSCs by incorporating Nitrogen-Titanium Dioxide (N-TiO2) composites synthesized via the Sol-Gel method [1]. The DSSCs were constructed using N-TiO2 composites in conjunction with VC, RP, and RM azo dyes. Nitrogen in the TiO2 matrix effectively reduced the band gap, leading to improved light absorption. The presence of Nitrogen dopants is expected to introduce additional energy levels within the TiO2 bandgap, enhancing light absorption and charge carrier separation, which are crucial factors for improved DSSC performance [2,3]. The current-voltage (I-V) characteristics of the DSSCs revealed significant variations in key performance metrics, including short circuit current (Isc), fill factor, and power conversion efficiency. Specifically, DSSCs utilizing N-TiO2 with VC-RP dye mixture achieved a higher efficiency of 0.349%, an Isc of 0.85 mA, and a fill factor of 44.59%, with Rs and Rsh values of 328.13Ω and 1637.18Ω, respectively [4]. These results underscore the potential of N-TiO2 composites, particularly when paired with optimized dye mixtures, to significantly enhance the electronic properties and overall efficiency of DSSCs.